The Existence of Children with Special Needs in Non-Inclusive Public Elementary Schools: A Study of Public Elementary Schools in Gladagsari District - Ersi Jati Semiyar; Karsono Karsono; Akhmad Arif Musadad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
The presence of children with special needs (CSN) in non-inclusive public elementary schools has become increasingly visible due to the limited number of inclusive schools and the growing demand for equitable education services. This study aims to describe the existence of CSN in non-inclusive public elementary schools in Gladagsari District based on 2025 recapitulation data. The study employed a descriptive qualitative approach using secondary data collected in July and November through documentation and data compilation techniques. Data were analyzed using a descriptive-comparative method to examine changes in the number, distribution, and types of special needs identified. The findings indicate an increase in identified CSN, with slow learners as the dominant category. This trend reflects improved awareness among schools; however, it has not been supported by adequate educational readiness, including the provision of special education services and adaptive learning strategies, highlighting the need for stronger inclusive education policies.